THE INFLUENCE OF LONG TIME OF BUSINESS, PLACE OF BUSINESS AND WORKING HOURS ON THE INCOME OF VEGETABLE TRADERS IN THE TRADITIONAL MARKET, WONOKROMO SUB-DISTRICT, SURABAYA CITY - Suryati Eko Putro (Jurnal Ekonomi, 2022)
This study aims to examine the effect of business capital, business location, length of business, and working hours on the income of fruit traders in the Traditional Market, Wonokromo District, Surabaya City. This research was a quantitative research. Using the statistical method used was multiple linear regression analysis. The author used the questionnaire and interview methods to collect data from 65 selected respondents, whose trading kiosk was located in the nearest traditional market to the Wonokromo Railway Station. The object of this research was the fruit traders at the Darmo Trade Center (DTC) Market, Mangga Dua and Bendul Merisi. The variables of business location, length of business and working hours have a simultaneous effect on the fruit traders’ income in the Traditional Market, Wonokromo District, Surabaya City. And partially on business capital, business location, length of business that influence and affect the fruit traders income and working hours which do not affect the income of fruit traders in the Traditional Market, Wonokromo District, Surabaya City